No end of conflict : rethinking Israel-Palestine - Alpher, Joseph (Rowman and Littlefield, 2016)
Yossi Alpher explains how Israel entered its current situation of growing international isolation, political stalemate, and gathering messianic political influence. He investigates the inability of Israelis and Palestinians to make peace and end their conflict before suggesting ways to moderate and soften the worst aspects of the situation.